METHODS OF DEVELOPING MOTIVATION IN STUDENTS THROUGH THE PHILOSOPHICAL AND PSYCHOLOGICAL ANALYSIS OF LITERARY WORKS - Yorqin Kholniyozovich Djurayev (European Science Publishing, 2024)
Philosophical and psychological analysis is a methodological approach to examining a person’s motivation, aimed at developing their thinking and fostering motivation. Similar to other methods, this approach utilizes motivation techniques and draws upon motivation theory.
Keywords: Philosophical and psychological analysis, motivation, needs, training, educational activities.